2012
DOI: 10.1002/chem.201103038
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Route to (+)‐Tedanolide and Analysis of Its Subtle Effects Controlling Conformation and Biological Behaviour

Abstract: The improved synthesis of the antitumor compound (+)-tedanolide is described through an aldol coupling of bis-ketone 7. This modification shortens the synthetic steps in the endgame and provides rapid access to this biologically important natural product. Additionally, it serves as a probe in order to unravel the conformational effects that impede or enable its successful synthesis. Having this way access to des-epoxy-tedanolide, its biological characterization surprisingly unravelled the mode of action to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…DARTS results suggest that it possibly binds to eEF2 kinase [ 24 ]. Desepoxy-tedanolide was shown to induce a phosphorylation of eEF2 and of eIF2α, but the primary target is not yet known [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…DARTS results suggest that it possibly binds to eEF2 kinase [ 24 ]. Desepoxy-tedanolide was shown to induce a phosphorylation of eEF2 and of eIF2α, but the primary target is not yet known [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dissection of the lactone linkage leads to linear fragment 13 , which could be generated from diketo fragment 14 and aldehyde fragment 15 (Scheme ). Diketone 14 , an advanced intermediate of Roush's synthesis of tedanolides with the C(5) ketone installed was synthesized earlier by our group and would be employed in the synthesis of desepoxy‐isotedanolide ( 11 ) 13…”
Section: Resultsmentioning
confidence: 99%
“…With 7 , we have already shown that the mode of action resembles that of the candidaspongiolides rather than 13‐deoxytedanolide 12. As seen with candidaspongiolide,4a desepoxytedanolide ( 7 ) induces the phosphorylation of the eukaryotic initiation factor eIF2α and as a consequence the cap‐dependent initiation of translation should be inhibited.…”
Section: Methodsmentioning
confidence: 95%
“…[12] As seen with candidaspongiolide, [4a] desepoxytedanolide (7)i nduces the phosphorylation of the eukaryotic initiation factor eIF2a and as ac onsequence the cap-dependent initiation of translation should be inhibited.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation